Les ressources lexicales dans les langues contrôlées - Bogacki, Krzysztof (Neophilologica, 2010)
This article deals with the lexicon, which is an important part of controlled languages. It is designed so as to increase readability of texts written using this subset of language by reducing their ambiguity and complexity. It is shown that developing a controlled language lexicon by severely reducing its size, thus eliminating some lexemes and approving only some of the possible meanings leads to conflicts. Very often these arise between general grammatical principles governing a controlled language and the terms to be included in the lexicon.